Effect of pomegranate juice (Punica Granatum) on behavioral patterns of intake in rats with induced diabetes - Valdés Miramontes, Elia Herminia; Virgen-Carrillo, Carmen Alejandrina; Martínez Moreno, Alma Gabriela; Pineda-Lozano, Jessica Elizabeth; Fonseca-Bustos, Verónica (Acta Universitaria, 2019)
Evidence on the alternative treatment of diabetes mellitus is now growing through functional foods such as pomegranate juice. Most studies focus on the physiological effect of juice when administered by gavage to diabetic rats. The objective was to evaluate the effect of free access to pomegranate juice exposure on the consumption of liquids, food intake, and body weight in diabetic rats. Two groups of six healthy rats and six hyperglycemic rats, induced with 60 mg/kg of intraperitoneal streptozotocin, were exposed to pomegranate juice, water, and food for 21 days. The results showed significant differences (p < 0.05) in fluid consumption and body weight in both groups. There were no significant differences in food intake (p > 0.05). The free access exposure to pomegranate juice showed its acceptance and generated behavioral differences in the intake.